2022
DOI: 10.3390/diagnostics12081835
|View full text |Cite
|
Sign up to set email alerts
|

Improved Task Performance, Low Workload, and User-Centered Design in Medical Diagnostic Equipment Enhance Decision Confidence of Anesthesia Providers: A Meta-Analysis and a Multicenter Online Survey

Abstract: Decision confidence—the subjective belief to have made the right decision—is central in planning actions in a complex environment such as the medical field. It is unclear by which factors it is influenced. We analyzed a pooled data set of eight studies and performed a multicenter online survey assessing anesthesiologists’ opinions on decision confidence. By applying mixed models and using multiple imputation to determine the effect of missing values from the dataset on the results, we investigated how task per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Finally, we examined participants' perceived decision confidence (binary as confident or unconfident) and perceived workload during the simulations [17,18]. We measured the workload using the raw National Aeronautics and Space Administration Task Load Index (NASA TLX).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we examined participants' perceived decision confidence (binary as confident or unconfident) and perceived workload during the simulations [17,18]. We measured the workload using the raw National Aeronautics and Space Administration Task Load Index (NASA TLX).…”
Section: Discussionmentioning
confidence: 99%
“…Free mental capacity is necessary to build optimal situation awareness [ 24 ]. In particular, in stressful situations, this should not be compromised by complicated data interpretation [ 39 ]. One way to increase situation awareness is through user-centred design.…”
Section: Discussionmentioning
confidence: 99%
“…It leads to a reduction in errors and an improvement in productivity, acceptance and user satisfaction [ 24 ]. There are some examples of such technologies based on the principles of situation awareness and user-centred design [ 39 , 40 , 41 ]. To help healthcare providers interpret the results of viscoelastic coagulation tests, Visual Clot, a new technology for alternative presentation of thromboelastometry data has been developed.…”
Section: Discussionmentioning
confidence: 99%
“…Streamlining this mental model creation process was likely also responsible for the improved confidence and reduced perceived workload observed with VB. Pooled analyses found that task performance was proportional to perceived diagnostic confidence and inversely proportional to workload [ 28 , 37 ]. Justified diagnostic confidence is vital because clinicians who feel justifiably confident can make better and faster decisions.…”
Section: Discussionmentioning
confidence: 99%